Advantageous Online Learning During Covid-19 Pandemic: Why Parents Disbelieve? - Armeria Wijaya; Vega Hesmatantya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
Parents' expectations for children's educational attainment must be restrained by Covid-19 in 2020. In Indonesia, the virus has interfered with all levels of school to reform the mode of learning. An immediate decision made by the Ministry of Education was to implement full online learning. This situation uncovers obstacles that children and parents undergo. Even though the advantages of the policies have been perceived and published, the stakeholders need to express the problems too. This paper will exhibit parents’ disbelief toward online learning. The survey using questionnaire had been administered to 200 parents of elementary level students of Muhammadiyah Schools in Surabaya, Indonesia. The results show parents’ disbelief issues. Online learning is believed as burdensome to parents and children. It is also ineffective in accommodating competencies such as academic, affective, spiritual competencies, as well as talents and interests. Interviews were then conducted to investigate the factors: parents own limited time to assist children in studying, numbers of the family own limited gadget facilities, and children need to meet their teacher directly to understand the lesson. Finally, the implication after parents’ disbelief is revealed. Parents were becoming more emotional to the children along with their demotivation to the online learning as well as the lower academic, affective, and spiritual competence.